FEATURES OF STIMULATED EMISSION OF A MEROCYANINE DYE IN THE PORES OF ANODIZED ALUMINUM - Ibrayev, N.Kh.; Afanasyev, D.A.; Omarova, G.S. (KU Publ., 2021)
The results of the study of the spectral-luminescent properties and the generation of stimulated emission of merocyanine dye molecules in a porous aluminum oxide films are presented. The addition of silver nanoparticles to the porous aluminum oxide films leads to an increase in the absorption cross section and an increase in the quantum yield of dye fluorescence in the alumina films. However, in the alumina films with silver nanoparticles, the generation of stimulated emission of dye molecules was not detected. We also studied the effect of polymethyl methacrylate polymer deposited on the surface of the alumina films with a dye on the spectral-luminescent properties and generation of stimulated emission of this dye. An increase in the optical density in the absorption band of the dye and an increase in the fluorescence intensity in samples with a deposited polymethyl methacrylate film are observed. The generation threshold of polymethine dye is reduced by a factor of 40 in the porous aluminum oxide sample with polymethyl methacrylate.
Keywords: porous aluminum oxide; merocyanine dye; electrochemical anodizing; stimulated emission; polymethyl methacrylate